1981
DOI: 10.2307/3027181
|View full text |Cite
|
Sign up to set email alerts
|

Factoring Factorials

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Mathematical Association of America is collaborating with JSTOR to digitize, preserve and extend access to The Two-Year College Mathematics Journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The prime factorization formula of n! provided in [15] can be summarized as follows: To acquire the prime factorization of n!, we must find, for each of these primes p, the exponent g p of the greatest power of p that divides n!. The formula is connected to the relationship between n, p, and g p .…”
Section: Proofmentioning
confidence: 99%
“…The prime factorization formula of n! provided in [15] can be summarized as follows: To acquire the prime factorization of n!, we must find, for each of these primes p, the exponent g p of the greatest power of p that divides n!. The formula is connected to the relationship between n, p, and g p .…”
Section: Proofmentioning
confidence: 99%
“…In this study, it was shown that there do not exist positive integers m and n that satisfy equation (2). For more versions of Brocard-Ramanujan Diophantine equation, see in [6,8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%